Optimization of Fermented Tofu with High Isoflavone Content through Variation of Inoculum Percentages and Ratios of Lactobacillus plantarum, Lactobacillus acidophilus, and Leuconostoc mesenteroides - Dea Indriani Astuti; Zahra Noviana (Institute for Research and Community Services (LPPM) ITB, 2013)
Tofu is a traditional food that can be found in several countries, such as Indonesia and Japan. Tofu is often made using the backslopping method, which brings the risk of pathogenic microorganism contamination and can lead to failure in production. Standardization of the production process is necessary in order to yield highly nutritious tofu that is safe to be consumed. In this research, standardization was investigated by variation of the inoculum percentages and ratios of Lactobacillus plantarum (a), Lactobacillus acidophilus (b), and Leuconostoc mesenteroides (c). The inoculum percentages used in this research were 7.5%, 10%, and 12.5%, while the inoculum ratios between a, b, and c were (a:b:c) 2:1:1; 1:2:1; 1:1:2; and 1:1:1. The optimum inoculum ages for a, b, and c were 8, 6, and 2 hours respectively. The highest growth rates of a, b, and c were 0.060h-1, 0.054h-1, and 0.092h-1 respectively. The highest lactic acid production rates of a, b, and c were 0.072%h-1, 0.063%h-1, and 0.126%h-1 respectively. The inoculum percentage and ratio that produced the highest isoflavones content was 12.5%(2:1:1), with the highest bacterial population growth rate being 0.019h-1, the highest formation rate of lactic acid being 0.045%h-1, and the isoflavone aglycones level being 0.445 mg/mL.